Leaving the rice fields but not the countryside: Gender, livelihood diversification and pro-poor growth in rural Viet Nam - Naila Kabeer; Tran Thi Van Anh (United Nations Research Institute for Social Development (UNRISD), 2000)
In the late 1980s, Viet Nam initiated a programme of 'economic renovation', doi moi, to promote the transition from a centrally planned to a market-based economy. The key goals of the policy package were economic growth and social development, while the key means included decollectivization of agriculture, price liberalization, devaluation to achieve more realistic exchange rates, reduction of public sector employment and a concomitant promotion of private sector enterprise. The reforms were remarkably successful. Annual GDP growth rates rose, while poverty declined. Exports performed strongly, increasing at more than 30 per cent per annum after 1988. However, challenges remain. Rates of per capita growth are still low, as Viet Nam has a high ratio of labour relative to other factors of production, including physical capital, infrastructure, land and natural resources. The expansion of employment opportunities poses a major challenge for state policy. There is also concern that sections of the population have not benefited from the transition to the market economy, and that the pre-reform pattern of low rates of economic growth combined with 'shared' poverty is being replaced by higher rates of growth but greater inequalities in income and opportunities. Poverty has remained a rural phenomenon in Viet Nam, and there is considerable underemployment in the countryside. With the lifting of restrictions on population mobility, flows of migration have been rising, from rural to urban areas and from the northern mountainous areas to the south. Rural employment and poverty reduction have consequently received particular attention in policy discussions. The objective is to encourage the rural population to 'leave the rice fields but not the countryside'. The increase of small farm productivity, the diversification of rural livelihoods and income sources, backed by improvements in rural roads and infrastructure, are seen to hold the key to achieving this objective. This paper is concerned with the interrelated issues of poverty, prosperity and diversification of rural livelihoods, which are considered central to the achievement of rural development. It explores these issues from a gender perspective. Gender-specific information could help to establish whether policies to promote economic growth and poverty reduction in the countryside might be more effective if gender were taken more explicitly into account. The authors begin with a general discussion of the concepts of household livelihoods and livelihood diversification, and then focus on gender aspects. The primary data on rural households in north and south Viet Nam are then used for a detailed empirical analysis of household livelihoods in the study areas. The analysis of livelihood strategies at the household level provides insights into the distribution of poverty and prosperity. There were certain north-south differences, in that households were generally better off in income terms in the south than in the north. The size of landholdings, access to credit and ownership of productive assets were all important determinants of household per capita income. The diversity of activities was a more critical determinant of per capita income than the number of economically active members per household. The gender-disaggregated analysis suggested that it was diversification into off-farm activities, rather than diversity per se, which explained higher levels of household income. It also suggested that, despite women's longer hours of work in domestic and childcare activities, marginal returns to their off-farm activities were very similar to those of men. Women's ability to diversify out of farming was more strongly associated with household well-being than that of men. The gender division of roles and responsibilities, and the kinds of preferences and priorities that it might have given rise to, might explain this differentiated impact on well-being. The analysis also suggested that determinants of the ability to diversify varied somewhat by gender. And the disaggregated analysis confirmed that the gender division of labour was not rigidly enforced in Viet Nam, but varied by geographical location and household circumstances. While policy makers in Viet Nam do not have to be persuaded of the importance of livelihood diversification in their efforts to promote growth and reduce poverty, the authors' findings provide a number of rationales as to why their efforts would be improved by more explicit attention to gender. The first rationale relates to rural growth and rests on the fact that women's ability to diversify out of farming is as important as that of men in generating rural income. The second rationale relates to household well-being. The study suggests that women's ability to diversify into off-farm activities has stronger and more consistent implications for the well-being of rural households. The third rationale links to poverty reduction. Households in which women are confined to farming (particularly to the farming of subsistence crops) and households in which women have only been able to diversify into waged employment are systematically poorer than the rest. In addition, female-maintained households tended to be poorer than the rest. The fourth rationale links to equity considerations. Rural women are able to achieve positive economic and well-being achievements only through extremely long hours of work and very little rest or leisure compared to men. Interventions to ease women's work burdens would clearly have equity as well as productivity effects.
Keywords: 330